1999
DOI: 10.1136/bmj.319.7224.1534
|View full text |Cite|
|
Sign up to set email alerts
|

Hypericum extract versus imipramine or placebo in patients with moderate depression: randomised multicentre study of treatment for eight weeks   Commentary: Has hypericum found its place in antidepressant treatment?

Abstract: Objectives To assess the efficacy and safety of hypericum extract (STEI 300, Steiner Arzneimittel, Berlin) compared with imipramine and placebo in patients in primary care with a current episode of moderate depression. Design Randomised, double blind, multicentre, parallel group trial for 8 weeks. Setting Trained panel of 18 general practitioners from four German states: Bavaria, Berlin, Rhineland Palatinate, and Saxony. Participants 263 patients (66 men, 197 women) with moderate depression according to ICD-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(118 citation statements)
references
References 12 publications
1
112
0
5
Order By: Relevance
“…There were 890 participants in SSRI studies, 596 in TCA studies, and 1,267 patients on placebo (Table 1). [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Of the 5 possible SSRIs available, 2 studied sertraline, 3 studied escitalopram (a precursor of citalopram), and 1 studied citalopram. Of the TCAs available, 2 studied dothiepin, 4 studied amitriptyline, 2 studied mianserin, and 3 studied imipramine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 890 participants in SSRI studies, 596 in TCA studies, and 1,267 patients on placebo (Table 1). [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Of the 5 possible SSRIs available, 2 studied sertraline, 3 studied escitalopram (a precursor of citalopram), and 1 studied citalopram. Of the TCAs available, 2 studied dothiepin, 4 studied amitriptyline, 2 studied mianserin, and 3 studied imipramine.…”
Section: Resultsmentioning
confidence: 99%
“…We also performed a funnel plot analysis to check for publication bias. There were a number of defi nitions for outcomes we described as "improvement": 4 defi nitions used ≤50% reduction in the Montgomery-Asberg Depression Rating Scale (MADRS), [16][17][18][19] ≤50% reduction in Hamilton Depression Rating Scale (HAMD), 20 ≤7 on the HAMD scale, 21 and ≤4 points on HAMD 22 ; and 3 defi nitions used global evaluation of improvement.…”
Section: Data Synthesismentioning
confidence: 99%
“…Some stud ies have dem on strated that St John's wort ef fectively treats mi nor and mild de pres sion and some times has fewer side ef fects than an ti de pres sant treat ment (13)(14)(15). Perceived ef fi cacy may be a mo ti va tion for vis it ing AM…”
Section: Discussionmentioning
confidence: 99%
“…Ad di tionally, AM approaches have not been tested suf fi ciently (12). Some stud ies as sert that AM may be as ef fec tive as con ven tional an ti depres sant treat ment among pa tients with mild and mod er ate de pres sion (13)(14)(15). A re cent ran dom ized, dou ble-blind, placebo-con trolled clin i cal trial found that a widely used herbal prod uct, St John's wort (Hypericum perforatum), was not effec tive for treat ment of ma jor de pres sion (16).…”
mentioning
confidence: 99%
“…Needless to say, efficacy studies try very hard to avoid these pitfalls, using various techniques. From the provider's perspective, these techniques include having therapists attend training sessions so that they can learn to perform the therapy systematically (9), using treatment manuals that detail what should and should not be done during the sessions (10), taperecording the sessions so that they can later be checked for adherence to the treatment protocol (11), having fixed dosing regimens or algorithms in drug trials (12), or having a fixed number of therapy sessions (13). Some surgical trials even go so far as to drop surgeons or centres that have high perioperative mortality or infection rates (14).…”
Section: The Interventionmentioning
confidence: 99%